Iron Deficiency in Seagrasses and Macroalgae in the Red Sea Is Unrelated to Latitude and Physiological Performance - Anton, Andrea; Hendriks, Iris E.; Marbà, Núria; Krause-Jensen, Dorte; Garcias-Bonet, Neus; Duarte, Carlos M. (Frontiers in Marine Science, 2018)
Iron can limit primary production in shallow marine systems, especially in tropical waters characterized by carbonated sediments, where iron is largely trapped in a non-available form. The Red Sea, an oligotrophic ecosystem characterized by a strong N-S latitudinal nutrient gradient, is a suitable setting to explore patterns in situ of iron limitation in macrophytes and their physiological performance under different iron regimes. We assessed the interactions between environmental gradients and physiological parameters of poorly-studied Red Sea macrophytes. Iron concentration, chlorophyll a concentration, blade thickness, and productivity of 17 species of macrophytes, including 7 species of seagrasses and 10 species of macroalgae, were measured at 21 locations, spanning 10 latitude degrees, along the Saudi Arabian coast. Almost 90% of macrophyte species had iron concentrations below the levels indicative of iron sufficiency and more than 40% had critically low iron concentrations, suggesting that iron is a limiting factor of primary production throughout the Red Sea. We did not identify relationships between tissue iron concentration, chlorophyll a concentration and physiological performance of the 17 species of seagrass and macroalgae. There was also no latitudinal pattern in any of the parameters studied, indicating that the South to North oligotrophication of the Red Sea is not reflected in iron concentration, chlorophyll a concentration or productivity of Red Sea macrophytes.